Inflorescences of the Bromeliad Vriesea friburgensis as Nest Sites and Food Resources for Ants and Other Arthropods in Brazil - Volker S. Schmid; Simone Langner; Josefina Steiner; Anne Zillikens (Psyche: A Journal of Entomology)
For the first time, the usage of bromeliad inflorescences as nesting sites for ants and other arthropods was studied. Frequencies of occurrence of nests were recorded from hollow stems of dried infructescences of the bromeliad Vriesea friburgensis on Santa Catarina Island, southern Brazil. Three habitat types were studied: miconietum and two types of restinga, one with low (restinga-low) and one with high vegetation cover (restinga-high). Additionally, flower visitation by ants was examined in restinga-low. Out of 619 infructescences, 33% contained nests. Ants were the most frequent occupants (82–96% of nests), followed by termites (3–18%) and bees (0–0.6%). Species accumulation curves and diversity indices indicate that the diversity of stem-occupying ant species is highest in restinga-low (eight species observed, 18 predicted) and lowest in restinga-high (four observed and predicted). Highest similarity of compositions of infructescence-inhabiting ant species was recorded between miconietum and restinga-high, lowest between restinga-low and restinga-high. Similarity between compositions of inflorescence-visiting and infructescence-inhabiting species in restinga-low was even higher (compared with the cases described in the previous sentence) although 50% of the involved species were present in only one of the samples. Altogether, our results indicate that inflorescences are important resources for ants and other nest-building insects from flowering season to past-fruiting season.